Bioinspired design of amphiphilic particles with tailored compartments for dual-drug controlled release. Issue 8 (4th February 2020) - Qin, Juanrong; Li, Zeke; Song, Botao
Abstract : A bioinspired strategy was proposed to fabricate amphiphilic particles with tailored compartments for dual-drug controlled release. Abstract : Inspired by the phenomenon of water droplets hanging over rose petals, we propose a green interfacial self-assembly strategy to construct amphiphilic particles with controllable compartments for dual-drug encapsulation and controlled release. The method involves fabrication of "sticky" superhydrophobic materials, assembling superhydrophilic hydrogel beads with "sticky" superhydrophobic material into an amphiphilic particle, and amphiphilicity induced self-organization of several small amphiphilic particles into a large-sized amphiphilic multicompartmental particle. With the employment of this approach, amphiphilic particles with tailored sizes, controllable morphology, and tunable numbers of compartments are successfully constructed. The formation process and the underlying principle are further clarified. We finally investigate the potential application of the amphiphilic multicompartmental particles to load both hydrophilic and hydrophobic species in separated domains and release them in a controllable manner without interference. This novel approach may offer a new route to generate amphiphilic materials for the purpose of multidrug combination therapy, multiple-cell encapsulation, and so on.